EVALUASI LEARNING PENYELENGGARAAN DIKLAT TEKNIS SUBSTANTIF MULTIMEDIA BAGI GURU MADRASAH ALIYAH DI BALAI DIKLAT KEAGAMAAN SEMARANG - Ratna Prilianti (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2017)
ABSTRAKPenelitian dilakukan dengan tujuan untuk mengetahui hasil belajar peserta diklat (Learning) pada penyelenggaraan Diklat Multimedia bagi Guru Madrasah Aliyah Di Balai Diklat Keagamaan Semarang. Penelitian ini merupakan penelitan deskriptif kuantitatif dengan metode survai. Model evaluasi yang digunakan adalah menggunakan Model Kirkpatrick yang memiliki kelebihan karena sifatnya yang menyeluruh, sederhana, dan dapat diterapkan dalam berbagai situasi pelatihan. Menyeluruh dalam artian model evaluasi ini mampu menjangkau semua sisi dari suatu program pelatihan. Dikatakan sederhana karena model ini memiliki alur logika yang sederhana dan mudah dipahami serta kategorisasi yang jelas dan tidak berbelit-belit. Sementara dari sisi penggunaan, model ini bisa digunakan untuk mengevaluasi berbagai macam jenis pelatihan dengan berbagai macam situasi. Dalam model Kirkpatrick, evaluasi dilakukan melalui empat level yaitu reaction, learning, behaviour dan impact. Pada penelitian ini hanya dilakukan untuk evaluasi level 2. Hasil belajar peserta diklat (Learning) pada aspek sikap dalam kategori sangat baik dengan rata-rata 88,54, aspek pengetahuan dalam kategori baik dengan rata-rata 82,07 dan pada aspek ketrampilan dalam kategori sangat baik dengan rata-rata 85,68.  Hasil belajar (learning) peserta diklat dapat ditingkatkan lagi dengan menggunakan metode tutor sebaya. Evaluasi pelaksanaan diklat juga perlu dilakukan untuk level 1 (reaksi), level 3 (perilaku kerja) dan level 4(dampak) melalui kegiatan evaluasi pasca diklat.Kata kunci : Evaluasi kickpatrick, learning, diklat  ABSTRACTThe study was conducted in order to determine the satisfaction of training participants (Reaction) to the educational aspect, the aspect of facilities, service aspects and determine learning outcomes of education and training (Learning) on the implementation Multimedia Training for Teachers Madrasah Aliyah In Balai Diklat Keagamaan Semarang. This research is descriptive quantitative research with survey method. Evaluation model used is using the Kirkpatrick model which has advantages because it is comprehensive, simple, and can be applied in a variety of training situations. Comprehensive evaluation model in the sense that it is able to reach all sides of a training program. Is said to be simple because this model has a logic flow that is simple and easy to understand and categorization clear and straightforward. In terms of usage, this model can be used to evaluate various types of training with a variety of situations. In Kirkpatrick's model, the evaluation was conducted through four levels, namely reaction, learning, behavior and impact. In this research is only done for the evaluation of level 1 and 2. Satisfaction of training participants (Reaction) to the educational aspects of the implementation Multimedia Training in both categories with a value of 87.62, aspects of the facility in the categories of both the value of 87.63, and service aspects in both categories with an average value of 89.38. Learning outcomes of education and training (Learning) on aspects of attitude in the excellent category with an average of 88.54, aspects of knowledge in both categories with an average of 82.07 and in the aspect of skill in the excellent category with an average of 85.68. In order satisfaction (reaction) participants in education and training can fit in either category it is necessary plus the frequency for extracurricular activities, set the menu to be more varied consumption and use the same software between training participants and trainers. Results of learning (learning) training participants can be increased further by using peer tutors. Evaluation of the implementation of the training are also needed for level 3 (work behavior) and 4 (impacts) through post-training evaluation activities.Keywords : kickpatrick evaluation, reaction, learning